Periorbital Oedema Associated with Hypothyroidism – A Case Report - Bushra R. Noaman; Abdullah M. Bazrgan (Indian Journal of Dental Research)
Introduction: Pituitary microadenomas are said to be common, with an incidence of 27%. Hypothyroidism causing periorbital oedema (PO) remains rare in the literature, but it is still within the etiological factors. Patient Concerns: This study presents a 53-year-old patient who presented with PO and visited the dental clinic to exclude dental infection. Diagnosis: Based on the evaluation of proper haematological and radiological investigations, pituitary microadenoma was identified with an abrupt increase in the thyroid stimulating hormone (TSH) level. Follow-up: The patient was followed with further studies to identify the primary cause of PO. It was concluded that the disruption in the drug regimen caused an increase in the TSH and led to PO rather than microadenoma.